Pakar Go Green Sdn Bhd [PGG] / Nur Rahimah Ibrahim - Ibrahim, Nur Rahimah (2021)
Pakar Go Green Sdn Bhd (PGG) is a bumiputera company which focusing on the product for agriculture industry. In this company analysis, it is focusing on the Bamboo Biochar that is produced by Pakar Go Green Sdn Bhd (PGG) to be investigated, identified and analysed along with their current problem and come out with solutions. According to this company, they use bamboo as biomass to produce biochar. Bamboo can help in soil stabilization but it cannot help to speed up the growth of crop. Thus, as the solution, use palm oil residue and plastic waste as the raw material to produce more quality biochar rather than bamboo. It is because in Malaysia, waste of palm oil such as palm kernel shell and empty fruit bunch is readily available and it rich of carbon content and contain high moisture than bamboo. Therefore, it will help to give nutrient in soil. For plastic waste, it contains high hydrogen reacts as catalyst to speed up the reaction. That means, by using plastic waste it not only gives nutrient toward soil but also help to enhanced the growth of plant.